Start Time and Worker Compensation: Implications for Staggered-Hours Programs - Eva Gutiérrez-i-Puigarnau; Jos N. van Ommeren (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
There is little known about the effects of staggered-hours programs that affect workers' working schedules to mitigate peak congestion. We examine the effect of workers' morning start times on their wages for Germany. In contrast to previous work based on cross-section data, we demonstrate that wages are not, or may be, a slight inverse U-shaped function of start time suggesting that staggered-hours programs might be welfare enhancing.
Keywords: J2; J3; R41; 330; Work start time; wage; productivity; staggered work hours; congestion; Arbeitszeitgestaltung; Arbeitsproduktivität; Lohnniveau; Engpass; Deutschland